2021
DOI: 10.33603/jnpm.v5i2.3641
|View full text |Cite
|
Sign up to set email alerts
|

Kemampuan Penalaran Matematis Siswa ditinjau dari Gender

Abstract: Tujuan penelitian ini yaitu untuk menganalisis profil kemampuan penalaran matematis pada siswa kelas VIII SMPN 10 Kendari berdasarkan perbedaan gender. Jenis penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif dan dilengkapi dengan pendekatan kualitatif. Data kualitatif dalam penelitian ini adalah hasil wawancara terhadap siswa. Sedangkan data kuantitatifnya diperoleh dari hasil pemberian tes kemampuan penalaran matematis. Data-data ini direduksi dan dianalisis untuk menjawab fokus penel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
1
0
1
Order By: Relevance
“…In the generalization indicator, female subjects fulfill this indicator because they are able to solve questions correctly in numbers 2 and 3. This agrees with research (Prajono et al, 2021) stated that female students were better in terms of generalization. For male subjects (YN) they are unable to generalize because the answers given are incomplete in number 2 but in number 3 the male subject is able to fulfill these indicators.…”
Section: English Versionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the generalization indicator, female subjects fulfill this indicator because they are able to solve questions correctly in numbers 2 and 3. This agrees with research (Prajono et al, 2021) stated that female students were better in terms of generalization. For male subjects (YN) they are unable to generalize because the answers given are incomplete in number 2 but in number 3 the male subject is able to fulfill these indicators.…”
Section: English Versionsupporting
confidence: 92%
“…The reasoning abilities of students who have differences in solving math problems can be caused by gender factors (Prajono et al, 2021). Gender also means a trait that exists in men and women which is described culturally and socially as women are softer and emotional while men are considered strong and rational (Awalyah et al, 2022).…”
Section: Preliminarymentioning
confidence: 99%
“…Researcher found the different result which conducted in previous study. The previous study focuses on mathematics reasoning skills based on gender (Prajono et al, 2021). Overall, in previous study found that male and female students' mathematics reasoning skills in solving trigonometry problems was low.…”
Section: Discussionmentioning
confidence: 97%
“…Konsep matematika harus dipelajari secara berurutan dan berkelanjutan. Akan tetapi, beberapa riset telah mengonfirmasi bahwa hasil belajar ataupun kemampuan matematika peserta didik di kota Kendari masih rendah (Afiatman et al., 2019;Fajar et al, 2019;Prajono et al, 2021;Misu & Hasnawati, 2023). Salah satu faktor penting yang mempengaruhi hasil belajar maupun kemampuan matematika peserta didik tersebut adalah pengetahuan dasar matematikanya (Palapasari et al, 2017;Anisa et al, 2019).…”
Section: Pendahuluanunclassified